2010
DOI: 10.4012/dmj.2009-127
|View full text |Cite
|
Sign up to set email alerts
|

Surface damages of zirconia by Nd:YAG dental laser irradiation

Abstract: The purpose of this study was to characterize the surface damages of zirconia by Nd:YAG dental laser irradiation through a systematic evaluation of the associated microstructural changes. Disk specimens of yttria-stabilized tetragonal zirconia polycrystals (Y-TZP) and ceria-stabilized zirconia/alumina nanocomposite (Ce-TZP/Al2O3 nanocomposite) were irradiated by Nd:YAG dental laser. The specimens were characterized using scanning electron microscopy, X-ray diffractometry, and wavelength dispersive X-ray spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
1
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 18 publications
(22 reference statements)
1
44
1
7
Order By: Relevance
“…Surface treatments such as air abrasion with aluminum oxide particles roughen the zirconia surface and increase the bond strength 17) . Other surface treatments of zirconia including laser treatment 18,19) , selective infiltration technique (SIE) 20) , hot etching solution 21,22) , nanostructured alumina coating 23) , and slurry-coated ceramic 24) have been developed to improve and enhance the surface roughened area to facilitate the mechanical interlocking of the ceramic and bonding resin.…”
Section: Introductionmentioning
confidence: 99%
“…Surface treatments such as air abrasion with aluminum oxide particles roughen the zirconia surface and increase the bond strength 17) . Other surface treatments of zirconia including laser treatment 18,19) , selective infiltration technique (SIE) 20) , hot etching solution 21,22) , nanostructured alumina coating 23) , and slurry-coated ceramic 24) have been developed to improve and enhance the surface roughened area to facilitate the mechanical interlocking of the ceramic and bonding resin.…”
Section: Introductionmentioning
confidence: 99%
“…Darkening of Y-TZP irradiated by a nanosecond laser should be a result of oxygen vacancies that were generated at high temperatures due to the release of oxygen atoms after substoichiometric dioxide formation, in which ZrO 2 became ZrO2-X 14,15) . Noda et al reported that a surface irradiated by a Nd:YAG laser became darkened and that the oxygen concentration clearly decreased, whereas the zirconium concentration increased 7) . Irradiated Y-TZP disks heated at 1,000°C for 5 min in air retuned to their original white color.…”
Section: Darkening Of the Machined Y-tzp Surface And Corresponding Comentioning
confidence: 99%
“…Metal parts such as frameworks can be joined by self-welding of the parts with combustible acrylic denture base resins and artificial composite teeth, which would be burned by conventional soldering 6) . Noda et al conducted an experiment involving the irradiation of zirconia using this Nd:YAG laser and examined the possibility of welding zirconia 7) . They reported that laser irradiation induced cracking on the surfaces of zirconia so Nd:YAG dental laser welding should not be performed on zirconia 7) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yttria-stabilized tetragonal zirconia polycrystals (Y-TZP) possess the requisite properties for use in dental restorations such as crowns, bridges, implant fixtures, abutments, and orthodontic brackets [1][2][3] . An intragranular type of Ce-TZP/Al2O3 nanocomposite was developed in which extremely fine Al2O3 and Ce-TZP particles are located within submicron-sized Ce-TZP and Al 2O3 grains respectively 4) .…”
Section: Introductionmentioning
confidence: 99%